A Dialogue on Relativism : Rorty and Feyerabend - Di Berardino, María Aurelia (2014)
In this article, I first explore the strategies proposed by two authors to escape or evade relativism: Richard Rorty and Paul Feyerabend. I then present Rorty's ethnocentric position and Feyerabend's anthropological version, with the ultimate goal to evaluate pros and cons of both points of view. Are Rorty or Feyerabend escaping relativism, evading relativism, or are they offering us an uncomfortable dilemma?